Question your teaspoons: tea-drinking, coping and commercialisation across three planning organisations. Issue 3 (27th May 2020) - Schoneboom, Abigail; Slade, Jason
Abstract : Purpose: As part of a wider ethnographic project that examines the significance of the public interest across three public and private sector UK planning organisations, this paper uses tea-drinking as a lens to understand structural forces around outsourcing and commercialisation. Reflecting across the five case studies, the analysis supports Burawoy's (2017) recent critique of Desmond's Relational Ethnography (2014). Using Perec's (1997[1973]) notion of the "infra-ordinary" as an anchor, it highlights the insight that arises from an intimate focus on mundane rituals and artefacts. Design/methodology/approach: The data were gathered through participant observation, chronicling the researchers' encounters with tea in each of the sites. A respondent-led photography exercise was successful at two sites. Up to 40 days of ethnographic fieldwork were carried out in each site. Findings: The tea-drinking narratives, while providing an intact description of discrete case study sites, exist in conversation with each other, providing an opportunity for comparison that informs the analysis and helping us to understand the meaning-making process of the planners both in and across these contexts. Originality/value: The paper contributes to critical planning literature (Murphy and Fox-Rogers, 2015; Raco et al., 2016), illuminating structural forces around outsourcing and commercialisation. It also generates methodological reflection on using an everyday activity to probe organisational culture and promote critical reflection on "weighty" issues across study sites.